Hameaux et villages paysans de la période romaine en plaine d’Alsace - Antonin Nüsslein; Pascal Flotté; Mathias Higelin; Muriel Roth-Zehner (Gallia)
The increasing number of excavations carried out over the past twenty years has considerably changed our vision of the countryside in Gaul and Roman Germany: agropastoral activity is not only founded on large Roman-style estates, such as palatial villas. Each region reveals a variety of settlement types, from very large villas to small farms. However, the areas are not inhabited exclusively by isolated settlements. The existence of villages and hamlets in rural areas is now acknowledged in various regions of Gaul and Roman Germany as well as in the British Isles. Research carried out in the plain of Alsace over the past twenty years has led to the discovery of sites that were composed of several agglomerated habitation units that can be described as villages and hamlets. The aim of this paper is to make known these singular rural settlements in the plain of Alsace. The article first presents six recently excavated sites. This section provides the reader with an overview of the characteristics and organisation of these sites, period by period, including plans. The second part of the article presents the different types of remains that make up these sites, sets out the general morphology and explains the evolution of these settlements. The cellars occupy a prominent place and represent between a quarter and a fifth of the total number of remains found at the sites. In this respect they are the key to the detection and analysis of these sites. Without the cellars these sites would remain almost undetectable. The other buildings identified at these five sites are significantly less numerous and are most often wells or furnaces. The foundations of the buildings associated with these cellars have not been identified (except for one site). These were certainly wattle-and-daub constructions, most often built on shallow, unfounded sandpits that were probably destroyed by taphonomic phenomena. In general the buildings in these settlements are still poorly known. Production structures, tools and various indicators that would identify the economic activities carried out at these sites are scarce. However, agropastoral activities seem to play an important role. The third part of the article focuses on the morphology and evolution of the sites. It is not possible to include the remains that make up these sites in the traditional classification schemes used for ancient rural settlements. The concentration of many contemporary cellars or wells within the same site (which form several occupation units) in some phases is not found in isolated settlements. Moreover, their morphology does not correspond to that of the villae or of the isolated farms found elsewhere in Alsace or Lorraine. At their peak (generally between the mid-2nd c. and the first half of the 4th c. AD) the sites extend over a minimum distance of 100 to 150 m. The different elements which make up these settlements are distributed across the area in a more or less dense way and according to various patterns. Two types of organisation can be distinguished, but it should be noted that the analysis of settlement morphology is biased as a result of the size and division of the observation windows. The first category includes settlements in which the occupation units develop in a linear and rather loose manner, probably along pathways which have not been preserved. The second type of organisation concerns settlements characterised by a short distance, less than 25 m, between the different cellars and buildings. According to the data collected within the excavation windows the clustered form mainly appears from the second half of the 2nd c. AD on. Two sites with possible clustered occupations are dated as early as the La Tène D period or to the beginning of the Early Empire. The other sites extended rapidly, but they were hardly founded ex nihilo. They last a maximum of two hundred years and undergo several phases of expansion. Almost all the sites presented thus show a trajectory that leads them from an isolated settlement, at least from a small and modest occupation, to a clustered settlement. In some cases a clustered rural settlement developed in the same location during the 6th-7th c. AD, after an apparent hiatus of several decades. This vision of the evolution of the hamlets remains uncertain because it is highly disturbed, in our opinion, by the possible displacement of settlements during their evolution. Indeed, the excavation windows do not always make it possible to assess the settlements, and their probable movements, in their entirety. Thus, the presence of gaps between certain phases, the absence of an occupation prior to the 2nd c. AD and the sometimes rapid emergence of a clustered settlement cannot be ascertained for all sites. The fourth part of the article presents the geographical context and socio-economic aspects of the villages and hamlets. The examples of rural settlements presented here are almost all located west of Strasbourg, in the area of the lower Bruche valley and in the Kochersberg area. Nevertheless, fieldwalks, ancient data and surveys make it possible to identify a potentially large number of them (more than forty for the moment) distributed over a large area between Sélestat, Strasbourg and Saverne. The verification of data from ancient, still ongoing and new excavations will undoubtedly reveal that the phenomenon is much more widespread. Analysis of the geographical context close to the settlements of the lower Bruche valley shows that they develop almost systematically near a river (less than 250 m) but almost invariably on terraces or light slopes that protect them from flooding and wetland-related problems. Transition sectors were preferred, between very fertile soils (loess and silt) and more alluvial areas, favouring multiple agropastoral activities. In the best known archaeological areas of the Bruche valley there is one such settlement type every 2,5 km on average between the 2nd and 4th c. AD. This density reflects an intensive development of the territory in which isolated settlements seem rare. In the lower Bruche valley additional information on population dynamics is available thanks to the fieldwalks carried out over many years. The number of settlements increased from the La Tène period to the 1st c. AD, then gradually decreased from the 2nd c. to the 5th c. AD. Among these general trends the emergence of clustered settlements thus appears to coincide with this pivotal moment in the decline in the total number of settlements during the 2nd c. AD. There is currently little evidence to enable us to evaluate the social status of the inhabitants. In any case these establishments should not all be interpreted as settlements made up of poor farmers, positioned outside the Roman tradition, the networks and the economic functioning of the region. The richness and provenance, sometimes distant, of the material remains discovered in the homes, the decorative elements uncovered and the presence of baths in Obernai are convincing arguments in this respect. In addition, these indicators also show that these villages and hamlets had a sufficiently high production capacity to generate surpluses and thus played a significant, but not yet specified, role in the regional production system. A role that undoubtedly benefited the army present in Strasbourg, at the outlet of the Bruche plain. Finally, the last part of the article presents the initial hypotheses on the origin of the phenomenon of the strong presence of villages and hamlets in the plain of Alsace between the 2nd and the 4th c. AD. Several hypotheses are discussed: rural exodus, presence of veterans, changes in lifestyle, particular economic and social conception, etc. The high concentration of villages and hamlets, particularly in the Bruche valley, would indicate above all the existence of a strong regional cultural and social particularism the origins of which date back to before the Roman period.